2019
DOI: 10.1038/s41467-019-11325-3
|View full text |Cite
|
Sign up to set email alerts
|

Polarity signaling ensures epidermal homeostasis by coupling cellular mechanics and genomic integrity

Abstract: Epithelial homeostasis requires balanced progenitor cell proliferation and differentiation, whereas disrupting this equilibrium fosters degeneration or cancer. Here we studied how cell polarity signaling orchestrates epidermal self-renewal and differentiation. Using genetic ablation, quantitative imaging, mechanochemical reconstitution and atomic force microscopy, we find that mammalian Par3 couples genome integrity and epidermal fate through shaping keratinocyte mechanics, rather than mitotic spindle orientat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 82 publications
1
17
0
Order By: Relevance
“…2C, D), supporting the concept of Par3 MCKO melanocytes residing in a less differentiated state compared to control melanocytes. These results were also interesting in light of recent data by us and others obtained in keratinocytes, where Par3 complex proteins serve to maintain stemness features of epithelial cells [27,[29][30][31]. Our findings presented here instead uncover that in neural-crest derived melanocytes 'apical' polarity proteins promote differentiation, rather than stemness.…”
Section: Par3 Inactivation Leads To Reduced Differentiation Of Ife Mesupporting
confidence: 82%
See 1 more Smart Citation
“…2C, D), supporting the concept of Par3 MCKO melanocytes residing in a less differentiated state compared to control melanocytes. These results were also interesting in light of recent data by us and others obtained in keratinocytes, where Par3 complex proteins serve to maintain stemness features of epithelial cells [27,[29][30][31]. Our findings presented here instead uncover that in neural-crest derived melanocytes 'apical' polarity proteins promote differentiation, rather than stemness.…”
Section: Par3 Inactivation Leads To Reduced Differentiation Of Ife Mesupporting
confidence: 82%
“…We and others previously demonstrated that in keratinocytes the apical polarity proteins Par3 and aPKCregulate cell-cell adhesion [26], stem cell fate, spindle orientation and differentiation in the epidermis [27][28][29][30]. In the adult skin epithelium, Par3 and aPKCpromote balanced fate decisions and protect against premature epidermal differentiation, though likely through independent mechanisms [27,29,31,32]. While above work unravelled an emerging epithelialintrinsic role of polarity proteins, we recently also uncovered extrinsic functions of polarity proteins in the control of neighbouring melanocytes: Disturbed polarity signalling in the surrounding skin epithelium resulted in aberrant keratinocytemelanocyte adhesions, promoting melanocyte transformation and malignant progression in a melanoma mouse model [33].…”
Section: Introductionmentioning
confidence: 95%
“…Based on these findings, the activation of Rho1 upon loss of Baz might be causative for the phenotype observed. Interestingly, epidermal deletion of Par3A resulted in an inactivation of RhoA in keratinocytes 31 . This opposite effect might be explained by the post-mitotic nature of podocytes, as the upstream regulation of RhoA via Par3A in keratinocytes seems to be important to maintain mitotic accuracy 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, epidermal deletion of Par3A resulted in an inactivation of RhoA in keratinocytes 31 . This opposite effect might be explained by the post-mitotic nature of podocytes, as the upstream regulation of RhoA via Par3A in keratinocytes seems to be important to maintain mitotic accuracy 31 . Given that podocytes are very different in shape to keratinocytes, one may also envision that cycling of RhoA between active/inactive states might be important in regulating the cytoskeleton to help maintain the podocyte architecture.…”
Section: Discussionmentioning
confidence: 99%
“…In the developing fly wing disc, acto-myosin-dependent mitotic rounding is essential to keep division within the epithelial plane to prevent cell delamination and apoptosis (Nakajima et al, 2013). Similarly, in the mouse epidermis, reduced acto-myosin contractility leads to impaired spindle orientation and biases divisions toward the perpendicular axis, forcing ectopic differentiation (Dias Gomes et al, 2019), Interestingly, in this study disruption of mitotic rounding also led to defects in spindle formation including lagging chromosomes and tripolar divisions (Dias Gomes et al, 2019), similar to those seen in confined single cells (Lancaster et al, 2013). In addition to parallel/perpendicular division orientation, the angle of division within the epithelial plane can also affect tissue morphology, for example by promoting uniaxial growth and elongation or to relieve tissue tension (Wyatt et al, 2015).…”
Section: Mitotic Rounding In Tissue Homeostasis and Developmentmentioning
confidence: 99%